Bimetalloporphyrin / GO / TiO2 nanotube composite photocatalytic material and application thereof
By using bimetallic porphyrin/GO/TiO2 nanotube composite photocatalytic materials, the existing photocatalysts are solved, and the existing photocatalysts are low efficiency and difficult to control in CO2 reduction reactions are achieved, and efficient photocatalytic CO2 reduction and product selectivity are achieved. , has good stability and recyclability.
Patent Information
- Application Number
- CN202411553577.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-02
- Publication Date
- 2025-02-11
AI Technical Summary
The existing photocatalytic conversion efficiency of existing photocatalytic conversion in CO2 reduction reaction is low, product selectivity is difficult to control, and the reaction mechanism is insufficient.
Using bimetaloporphyrin/GO/TiO2 nanotube composite photocatalytic materials, Ni-CoTCPP, Ni-CoTCPP/TiO2NTs and Ni-CoTCPP/GO/TiO2NTs, the electronic structure of bimetaloporphyrin and the conductivity of GO are utilized. Improve photocatalytic activity and product selectivity.
The efficiency and product selectivity of photocatalytic CO2 reduction are significantly improved, the apparent quantum efficiency reaches 1.2%, and it has good stability and cyclability.
Smart Images

Figure CN119406451A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of nanomaterials and photocatalysis technology, and specifically to a bimetallic porphyrin / GO / TiO2 nanotube composite photocatalytic material and application thereof. Background Art
[0002] There are many ways to reduce CO2. In the long run, solar photocatalytic conversion of CO2 is a potential means to convert CO2 into value-added solar fuels, which can not only alleviate the global energy crisis, but also solve the greenhouse effect. Photocatalytic reduction of CO2 technology uses solar energy to excite semiconductor materials to produce highly active photogenerated electron-hole pairs, allowing the CO2 reduction reaction to proceed and generate organic compounds with great application value, such as CH4, CH3OH, HCHO and HCOOH. At present, the most basic factors restricting CO2 reduction are the high recombination rate of photogenerated electrons and holes, the low light absorption range and light utilization rate, the high catalyst cost and the poor product selectivity, so the successful preparation of effective photocatalytic materials is still the theme in the field of CO2 reduction. Summary of the invention
[0003] One object of the present invention is to provide a bimetallic porphyrin / GO / TiO2 nanotube composite photocatalytic material, which is used to solve the problems in the prior art of low photocatalytic conversion efficiency, difficult control of product selectivity and insufficient understanding of the reaction mechanism of photocatalysts in CO2 reduction reactions; another object of the present invention is to provide an application of the bimetallic porphyrin / GO / TiO2 nanotube composite photocatalytic material.
[0004] The technical solution adopted by the present invention to solve the technical problem is: the bimetallic porphyrin / GO / TiO2 nanotube composite photocatalytic material is prepared by the following preparation method: Step 1, preparation of Ni-CoTCPP: weigh 0.02 mmol of Ni (NO3)2・6H2O) and 10 mg of PVP, dissolve in a mixture of 18-30 mL of DMF and anhydrous ethanol to obtain solution A; then take 0.01 mmol of CoTCPP and dissolve it in a mixed solution of 6-10 mL of DMF and anhydrous ethanol, ultrasonically dissolve it in an ultrasonic cleaner for 10-20 min, and then take it out to obtain solution B; add solution B dropwise to solution A, and finally transfer the mixed solution to a 50 mL polytetrafluoroethylene-lined reactor, and react at 70-100°C for 2-4 h; after the reaction is completed, transfer it to a centrifuge tube, add anhydrous ethanol, wash and centrifuge to obtain the desired product Ni-CoTCPP; Step 2: Preparation of Ni-CoTCPP / TiO2NTs: Ni-CoTCPP was prepared at a concentration of 1×10 -5mol / L concentration was dissolved in DMF to prepare a bimetallic porphyrin solution; TiO2NTs were immersed in the porphyrin solution and magnetically stirred for 4-6 h, the titanium foil was taken out with tweezers, and dried at room temperature to obtain bimetallic porphyrin-sensitized TiO2NTs, namely Ni-CoTCPP / TiO2NTs; Step 3. Preparation of Ni-CoTCPP / GO / TiO2NTs: Immerse Ni-CoTCPP / TiO2NTs in a 0.5 mg / mL GO suspension, stir magnetically for 4-6 h, remove the titanium foil with tweezers, and dry at room temperature to obtain Ni-CoTCPP / GO / TiO2NTs.
[0005] In the mixed solution of DMF and anhydrous ethanol in the above scheme, the volume ratio of DMF to anhydrous ethanol is 3:1.
[0006] The preparation method of CoTCPP in the above scheme is: weigh 79 mg TCPP and 75 mg (CH3COO)2Co·4H2O powder, add 150-300 mL DMF and acetic acid mixed solution, reflux at 100-150 °C for 1-3 h, after the reaction is completed, cool and add 400-600 mL water to precipitate the product; filter, wash and dry to obtain CoTCPP.
[0007] In the mixed solution of DMF and acetic acid in the above scheme, the volume ratio of DMF to acetic acid is 1:1.
[0008] The preparation method of TCPP in the above scheme is: take 3.00 g of p-carboxybenzaldehyde and 60-90 mL of propionic acid, mix them and pour them into a three-necked flask with a capacity of 250 mL, and stir them under the action of a magnetic stirrer for 0.25-1 h; then heat to 100-150 ° C, measure 1.4 mL of freshly distilled pyrrole and 8-15 mL of propionic acid, mix them and add them dropwise into the three-necked flask, the dropping time is maintained at 5-15 min, heat to reflux for 3-5 h, and naturally cool to room temperature after the reaction is completed, continue to add 8-15 mL of ethanol and stir evenly, then place it in a 4 ° C cold water bath to react for 15-20 h; filter, rinse the filter cake with CH3OH solution for many times, and then use CH3OH to Soxhlet extraction on the filter cake until the washing liquid is clear, and the obtained purple filter cake is recrystallized with methanol-chloroform solution to obtain TCPP.
[0009] Preparation method of GO in the above scheme: 1) Dissolve 2 g of natural flake graphite and 2 g of NaNO3 in 92 mL of concentrated H2SO4 and stir in an ice bath for 10 min until uniform; 2) Slowly add 9 g KMnO4 in batches, control the system temperature at 0-5 °C and react for 2 h; 3) Then slowly raise the temperature of the water bath to 35 °C and continue the reaction for 2 h. Then add 90 mL of deionized water and raise the temperature to 98 °C for a constant temperature reaction for 0.5 h. 4) After cooling naturally to room temperature, add 180 mL of deionized water and drop 10 mL of 30% H2O2 into the solution until the solution turns bright yellow; 5) The solution was washed with 1 mol / L HCl and then centrifuged with deionized water until the pH value of the solution was close to 7.0. Finally, the supernatant was ultrasonically treated and dried to obtain GO.
[0010] Preparation method of TiO2NTs in the above scheme: 1) 1.5 cm² titanium foil was ultrasonically cleaned in acetone, anhydrous ethanol and deionized water for 15 min, and dried at room temperature; 2) Use the cleaned titanium foil as the anode electrode and the platinum foil as the counter electrode, immerse them in an electrolyte consisting of ethylene glycol, 2 vol% deionized water and 0.3 wt% NH4F, stir the electrolyte in a constant temperature water bath at 20 °C, adjust the constant voltage power supply voltage to 60 V for primary oxidation, and control the oxidation time to 0.5 h; 3) Place the titanium sheet after primary oxidation in deionized water and ultrasonically wash away the formed oxide film, rinse it clean and dry it; 4) The titanium sheet obtained in step 3) is subjected to secondary anodization according to the method of step 2), and after completion, the generated TiO2NTs are washed with deionized water and dried; 5) The dried TiO2NTs were calcined in a muffle furnace at 450 °C for 3 h at a heating rate of 2 °C / min to obtain TiO2NTs.
[0011] The above-mentioned bimetallic porphyrin / GO / TiO2 nanotube composite photocatalytic material is used for photocatalytic reduction of CO2.
[0012] Method for photocatalytic reduction of CO2 using bimetallic porphyrin / GO / TiO2 nanotube composite photocatalytic materials: The photocatalytic reduction CO2 device includes a photocatalytic reactor and a water vapor generator. The light source is placed above the photocatalytic reactor. The photocatalytic reactor and the light source are placed in a photocatalytic reaction protection cover. The light source is a 500 W xenon lamp light source. The CO2 gas pipeline is connected to the photocatalytic reactor after passing through the water vapor generator. The bimetallic porphyrin / GO / TiO2 nanotube composite photocatalytic material is placed on a titanium sheet, and the titanium sheet is placed in the photocatalytic reactor. Before the reaction, check the airtightness of the photocatalytic reduction CO2 device and remove the impurity gas in the photocatalytic reactor; During the reaction, CO2 gas passes through the water vapor generator and maintains a flow rate of 60 mL / min, so that the mixed gas formed by CO2 and water vapor enters the photocatalytic reactor. When the pressure of CO2 and water vapor in the photocatalytic reactor reaches 1.5 atm, the circulating cooling water pump is turned on to complete the photocatalytic reduction of CO2 under continuous illumination. Beneficial Effects
[0013] 1. The present invention constructs a bimetallic porphyrin / GO / TiO2NTs ternary composite material through the role of porphyrin in photosynthesis. Due to its excellent visible light absorption ability and stronger ability to generate and transfer photogenerated carriers, it achieves multiple goals in the field of photocatalytic CO2 reduction, improves photocatalytic activity, and can control product selectivity. It is of great significance for the comprehensive control of CO2 pollutant resource and energy in industrial waste gas and other environments.
[0014] 2. The composite photocatalytic material of the present invention forms an efficient composite photocatalytic system by compounding bimetallic porphyrin with TiO2NTs and introducing GO. Bimetallic porphyrin has a unique electronic structure and optical properties, which can enhance the absorption and utilization of light and improve the efficiency of photogenerated carrier generation. As a good photocatalyst carrier, TiO2NTs provides a large specific surface area and a suitable energy band structure, which is conducive to the photocatalytic reaction. The introduction of GO greatly improves the conductivity of the material, effectively promotes the separation and transmission of electron-hole pairs, thereby significantly improving the performance of photocatalytic reduction of CO2.
[0015] 3. The preparation method provided by the present invention is simple and easy, and does not require complicated equipment and process conditions. The preparation of TiO2NTs adopts a two-step anodization method, which is mature and stable and can produce high-quality TiO2NTs. The synthesis of bimetallic porphyrins can be achieved through conventional chemical reactions, and the reaction conditions are mild and easy to control. The preparation of GO adopts the Hummers method, which is a widely used preparation method and can produce GO with excellent performance. The raw materials used, such as titanium foil, porphyrin precursor, graphite, etc., are easy to obtain and have low cost, which is conducive to large-scale production and application. Therefore, the present invention has good application prospects and is expected to be widely used in the field of photocatalytic reduction of CO2. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 Schematic diagram of the preparation process of Ni-CoTCPP / GO / TiO2NTs.
[0017] Figure 2 TEM image of Ni-CoTCPP / GO / TiO2NTs.
[0018] Figure 3 These are the XRD patterns of GO, TiO2NTs, GO / TiO2NTs, Ni-CoTCPP / TiO2NTs and Ni-CoTCPP / GO / TiO2NTs in the present invention.
[0019] Figure 4 Schematic diagram of the photocatalytic CO2 reduction device.
[0020] Figure 5 This is the photocatalytic reduction CO2 performance diagram of different catalysts and GO / TiO2NTs prepared in Example 3.
[0021] Figure 6 This is the stability test diagram of Ni-CoTCPP / GO / TiO2NTs catalyst.
[0022] Figure 7 XRD patterns of Ni-CoTCPP / GO / TiO2NTs before and after 10 cycles.
[0023] In the figure: 1-mass flow meter; 2-bubbler; 3-bubbler temperature control and constant temperature system; 4-xenon lamp light source; 5-photocatalytic reactor; 6-bimetallic porphyrin / GO / TiO2 nanotube composite photocatalytic material. DETAILED DESCRIPTION
[0024] The present invention will be further described below in conjunction with the accompanying drawings: Example
[0025] The bimetallic porphyrin / GO / TiO2 nanotube composite photocatalytic material is prepared by the following preparation method: (1) Preparation of Ni-CoTCPP: Weigh Ni (NO3)2・6H2O (0.02 mmol) and PVP (10.0 mg) and dissolve them in a mixture of 18 mL DMF and anhydrous ethanol (V:V = 3:1) to obtain solution A. Then take CoTCPP (0.01 mmol) and dissolve it in a mixture of 6 mL DMF and anhydrous ethanol, ultrasonically dissolve it in an ultrasonic cleaner for 20 min, and then take it out to obtain solution B. Solution B was added dropwise to solution A, and finally the mixed solution was transferred to a 50 mL reactor with a polytetrafluoroethylene liner and reacted at 70°C for 2 h. After the reaction was completed, it was transferred to a centrifuge tube, an appropriate amount of anhydrous ethanol was added, and the mixture was washed and centrifuged for 10 min. After repeating 3 times, the desired product Ni-CoTCPP was obtained; (2) Preparation of Ni-CoTCPP / TiO2NTs: Ni-CoTCPP was prepared at a rate of 1×10 -5mol / L concentration was dissolved in DMF to prepare a bimetallic porphyrin solution. TiO2NTs were immersed in the porphyrin solution and magnetically stirred for 4 h. The titanium foil was removed with tweezers and dried at room temperature to obtain bimetallic porphyrin-sensitized TiO2NTs. (3) Preparation of Ni-CoTCPP / GO / TiO2NTs: Ni-CoTCPP / TiO2NTs were immersed in a 0.5 mg / mL GO suspension and magnetically stirred for 4 h. The titanium foil was removed with tweezers and dried at room temperature to obtain Ni-CoTCPP / GO / TiO2NTs.
[0026] The preparation method of TCPP in this embodiment is as follows: 3.00 g of p-carboxybenzaldehyde and 60 mL of propionic acid are mixed and poured into a three-necked flask with a capacity of 250 mL, and stirred for 0.25 h under the action of a magnetic stirrer; then heated to 100°C, 1.4 mL of freshly distilled pyrrole is measured and mixed with 10 mL of propionic acid, and then added dropwise into the three-necked flask, the dropping time is maintained at 5 min, heated to reflux for 3 h, and naturally cooled to room temperature after the reaction is completed, 10 mL of ethanol is continued to be added and stirred evenly, and the above mixture is placed in a 4°C cold water bath for reaction for 15 h; suction filtration is performed, the filter cake is rinsed with CH3OH solution for many times, and then the filter cake is subjected to Soxhlet extraction with CH3OH until the washing liquid is clear, and the obtained purple filter cake is recrystallized with methanol-chloroform solution to obtain TCPP.
[0027] The preparation method of CoTCPP in this embodiment is as follows: weigh 79 mg TCPP and 75 mg (CH3COO)2Co·4H2O powder, add them to 150 mL DMF and acetic acid mixed solution, reflux at 100°C for 1 h, and after the reaction is completed, cool and add 400 mL water to precipitate the product; filter, wash, and dry to obtain CoTCPP.
[0028] The test process of using this bimetallic porphyrin / GO / TiO2 nanotube composite photocatalytic material for photocatalytic reduction of CO2 is as follows: See also Figure 4The photocatalytic reduction CO2 device includes a photocatalytic reactor 5 and a water vapor generator. The light source is placed above the photocatalytic reactor 5. The photocatalytic reactor 5 and the light source are placed in a photocatalytic reaction protective cover. The light source uses a 500 W xenon lamp light source 4 as a light source for simulating sunlight. Since the xenon lamp will release heat when illuminated for a long time, it will affect the accuracy of the experiment. The circulating cooling water is used to reduce the reaction temperature; the CO2 gas pipeline is connected to the photocatalytic reactor 5 after passing through the water vapor generator, and a mass flow meter 1 is set before the CO2 gas pipeline enters the bubbler 2. The bimetallic porphyrin / GO / TiO2 nanotube composite photocatalytic material 6 is placed on a titanium sheet, and the titanium sheet is placed in the photocatalytic reactor 5; the water vapor generator is composed of a bubbler 2 placed in a bubbler temperature control and constant temperature system 3.
[0029] The specific operation steps are as follows: Select a titanium sheet of appropriate size loaded with a sample and place it in the photochemical reactor. First, check the airtightness of the experimental device, and pass N2 for pressure test to ensure that the photocatalytic reactor has a good sealing effect. Before illumination, purge the reactor with high-purity CO2 for 60 min to remove the impurity gas in the reactor, and then the CO2 gas passes through the water vapor generator and maintains a flow rate of 60 mL / min to ensure that CO2 is fully in contact with the water vapor in the water vapor generator, so that the mixed gas formed by CO2 and water vapor can enter the photochemical reactor in large quantities, so that the reaction raw materials are sufficient. When the pressure of CO2 and water vapor in the reactor reaches 1.5 atm, the reactor is sealed. Turn on the circulating cooling water pump, and after continuous illumination for a certain period of time, turn off the xenon light source, and use an Agilent gas chromatograph equipped with a hydrogen flame ionization (FID) detector and a thermal conductivity detector (TCD) to quantitatively analyze the content of the reduction product. Example
[0030] The bimetallic porphyrin / GO / TiO2 nanotube composite photocatalytic material is prepared by the following preparation method: (1) Preparation of Ni-CoTCPP: Weigh Ni (NO3)2・6H2O (0.02 mmol) and PVP (10.0 mg) and dissolve them in a mixture of 30 mL DMF and anhydrous ethanol (V:V = 3:1) to obtain solution A. Then take CoTCPP (0.01 mmol) and dissolve it in a mixture of 10 mL DMF and anhydrous ethanol. Ultrasonic dissolution in an ultrasonic cleaner for 10 min and then take it out to obtain solution B. Solution B was added dropwise to solution A, and finally the mixed solution was transferred to a 50 mL reactor with a polytetrafluoroethylene liner and reacted at 100°C for 2 h. After the reaction was completed, it was transferred to a centrifuge tube, an appropriate amount of anhydrous ethanol was added, and the mixture was washed and centrifuged for 10 min. After repeating 3 times, the desired product Ni-CoTCPP was obtained; (2) Preparation of Ni-CoTCPP / TiO2NTs: Ni-CoTCPP was prepared at a rate of 1×10 -5 mol / L concentration was dissolved in DMF to prepare a bimetallic porphyrin solution. TiO2NTs were immersed in the porphyrin solution and magnetically stirred for 6 h. The titanium foil was removed with tweezers and dried at room temperature to obtain bimetallic porphyrin-sensitized TiO2NTs. (3) Preparation of Ni-CoTCPP / GO / TiO2NTs: Ni-CoTCPP / TiO2NTs were immersed in a 0.5 mg / mL GO suspension and magnetically stirred for 6 h. The titanium foil was removed with tweezers and dried at room temperature to obtain Ni-CoTCPP / GO / TiO2NTs.
[0031] The preparation method of TCPP in this embodiment is as follows: 3.00 g of p-carboxybenzaldehyde and 90 mL of propionic acid are mixed and poured into a three-necked flask with a capacity of 250 mL, and stirred for 0.7 h under the action of a magnetic stirrer; then heated to 120°C, 1.4 mL of freshly distilled pyrrole is measured and mixed with 15 mL of propionic acid, and then added dropwise into the three-necked flask, the dropping time is maintained at 10 min, heated to reflux for 5 h, and naturally cooled to room temperature after the reaction is completed, 15 mL of ethanol is continued to be added and stirred evenly, and the above mixture is placed in a 4 °C cold water bath for reaction for 18 h; suction filtration is performed, the filter cake is rinsed with CH3OH solution for many times, and then the filter cake is subjected to Soxhlet extraction with CH3OH until the washing liquid is clear, and the obtained purple filter cake is recrystallized with methanol-chloroform solution to obtain TCPP.
[0032] The preparation method of CoTCPP in this embodiment is as follows: weigh 79 mg TCPP and 75 mg (CH3COO)2Co·4H2O powder, add them to 200 mL DMF and acetic acid mixed solution, reflux at 150 °C for 2 h, after the reaction is completed, cool and add 500 mL water to precipitate the product; filter, wash and dry to obtain CoTCPP.
[0033] In this embodiment, the test process of using the bimetallic porphyrin / GO / TiO2 nanotube composite photocatalytic material for photocatalytic reduction of CO2 is the same as that in Example 1. Example
[0034] Step 1: Preparation of Ni-CoTCPP: 1) Weigh Ni(NO3)2·6H2O (0.02 mmol) and PVP (10.0 mg) and dissolve them in 24 mL of a mixture of DMF and anhydrous ethanol (V:V = 3:1) to obtain solution A; 2) CoTCPP (0.01 mmol) was dissolved in a mixed solution of 8 mL DMF and anhydrous ethanol, and then ultrasonically dissolved in an ultrasonic cleaner for 10 min and then taken out to obtain solution B; 3) Add solution B dropwise to solution A, and finally transfer the mixed solution to a 50 mL polytetrafluoroethylene-lined reactor and react at 80 °C for 3 h; 4) After the reaction is completed, transfer to a centrifuge tube, add an appropriate amount of anhydrous ethanol, wash and centrifuge for 10 min, repeat 3 times to obtain the desired product Ni-CoTCPP.
[0035] The obtained product is Ni-CoTCPP. Under the above experimental conditions, the photocatalytic reduction of CO2 was tested. The reduction product analysis showed that the rate of photocatalytic CO2 reduction to produce CH4 was 4.918 μmol·cm -2 ·h -1 , the apparent quantum efficiency is 0.094%.
[0036] Step 2: Preparation of Ni-CoTCPP / TiO2NTs: 1) Ni-CoTCPP was prepared at 1×10 -5 mol / L concentrations were dissolved in DMF to prepare bimetallic porphyrin solutions.
[0037] 2) Immerse TiO2NTs in the prepared bimetallic porphyrin solution, stir magnetically for 5 h, remove the titanium foil with tweezers, and dry at room temperature to obtain bimetallic porphyrin-sensitized TiO2NTs.
[0038] The obtained product is Ni-CoTCPP / TiO2NTs. The photocatalytic reduction of CO2 was tested under the above experimental conditions. The reduction product analysis showed that the rate of photocatalytic CO2 reduction to produce CH4 was 52.27 μmol·cm -2 ·h -1 , the apparent quantum efficiency is 1.0%.
[0039] Step 3: Preparation of Ni-CoTCPP / GO / TiO2NTs: Ni-CoTCPP / TiO2NTs were immersed in a 0.5 mg / mL GO suspension and magnetically stirred for 5 h. The titanium foil was removed with tweezers and dried at room temperature to obtain Ni-CoTCPP / GO / TiO2NTs.
[0040] The obtained product is Ni-CoTCPP / GO / TiO2NTs. The photocatalytic reduction of CO2 was tested under the above experimental conditions. The reduction product analysis showed that the rate of photocatalytic CO2 reduction to produce CH4 was 61.55 μmol·cm-2 ·h -1 , the apparent quantum efficiency is 1.2%.
[0041] Preparation of GO in this example: 1) Dissolve 2 g of natural flake graphite and 2 g of NaNO3 in 92 mL of concentrated H2SO4 and stir evenly in an ice bath for 10 min; 2) Slowly add 9 g KMnO4 in batches, and keep the system temperature below 5 °C for 2 h; 3) Then slowly raise the temperature of the water bath to 35 °C and continue the reaction for 2 h. Then add 90 mL of deionized water to the solution and raise the temperature to 98 °C for a constant temperature reaction for 0.5 h. 4) After cooling naturally to room temperature, add 180 mL of deionized water and add 10 mL of H2O2 (30 wt%) dropwise to the solution until the solution turns bright yellow; 5) The solution was washed with 1 mol / L HCl and then centrifuged with deionized water until the pH value of the solution was close to 7.0. Finally, the supernatant was ultrasonically treated and dried to obtain GO.
[0042] The obtained product is GO. Under the above experimental conditions, the photocatalytic reduction of CO2 was tested. The reduction product analysis showed that the rate of photocatalytic CO2 reduction to produce CH4 was 1.257 μmol·cm -2 ·h -1 , the apparent quantum efficiency is 0.024%.
[0043] Preparation of TiO2NTs in this example: 1) 1.5 cm² titanium foil was ultrasonically cleaned in acetone, anhydrous ethanol and deionized water for 15 min, and dried at room temperature; 2) Use the cleaned titanium foil as the anode electrode and the platinum foil as the counter electrode, immerse them in an electrolyte consisting of ethylene glycol, 2 vol% deionized water and 0.3 wt% NH4F, stir the electrolyte in a constant temperature water bath at 20 °C, adjust the constant voltage power supply voltage to 60 V for primary oxidation, and control the oxidation time to 0.5 h; 3) After the first oxidation, the titanium sheet is placed in deionized water and ultrasonically washed to remove the formed oxide film, then rinsed and dried; 4) Perform secondary anodization under the same conditions, and then wash the generated TiO2NTs with deionized water and dry them; 5) The dried TiO2NTs were calcined in a muffle furnace at 450 °C for 3 h with a heating rate of 2 °C / min.
[0044] The obtained product is TiO2NTs. Under the above experimental conditions, the photocatalytic reduction of CO2 was tested. The reduction product analysis showed that the rate of photocatalytic CO2 reduction to produce CH4 was 7.153 μmol·cm -2 ·h -1 , the apparent quantum efficiency is 0.14%.
[0045] In this embodiment, the test process of using GO, TiO2NTs, Ni-CoTCPP / TiO2NTs and Ni-CoTCPP / GO / TiO2NTs for photocatalytic reduction of CO2 is the same as that in Example 1.
[0046] The present invention also uses GO / TiO2NTs for photocatalytic reduction of CO2 as follows: Preparation of GO / TiO2NTs: TiO2NTs were immersed in a 0.5 mg / mL GO suspension and magnetically stirred for 5 h. The titanium foil was removed with tweezers and dried at room temperature to obtain GO / TiO2NTs.
[0047] The obtained product is GO / TiO2NTs. The photocatalytic reduction of CO2 was tested under the above experimental conditions. The reduction product analysis showed that the rate of photocatalytic CO2 reduction to produce CH4 was 28.38 μmol·cm -2 ·h -1 , the apparent quantum efficiency is 0.54%.
[0048] Figure 3 The XRD patterns of samples GO, TiO2NTs, GO / TiO2NTs, Ni-CoTCPP / TiO2NTs and Ni-CoTCPP / GO / TiO2NTs are shown in Figure 1. The characteristic peak of GO at 2Ɵ=11° is the characteristic peak of the (001) plane of GO. The characteristic peak of GO appears in the XRD pattern of GO / TiO2NTs, indicating that GO has been successfully modified onto TiO2NTs. Since the sensitization of Ni-CoTCPP does not change the crystal form of TiO2, the XRD pattern of Ni-CoTCPP / GO / TiO2NTs has the same peak positions as those of TiO2NTs except for the characteristic peak of GO.
[0049] Under simulated sunlight, the photocatalytic activity of GO, Ni-CoTCPP, TiO2NTs, GO / TiO2NTs, Ni-CoTCPP / TiO2NTs and Ni-CoTCPP / GO / TiO2NTs photocatalysts in converting CO2 and water vapor into CH4 was investigated under the same experimental conditions. Figure 5The CH4 yield and quantum efficiency of all catalysts are shown. The rates of CH4 produced by photocatalytic CO2 reduction for samples GO, Ni-CoTCPP, TiO2NTs, GO / TiO2NTs, Ni-CoTCPP / TiO2NTs, and Ni-CoTCPP / GO / TiO2NTs are 1.257 μmol·cm -2 ·h -1 、4.918 μmol·cm -2 ·h -1 、7.153 μmol·cm -2 ·h -1 、28.38 μmol·cm -2 ·h -1 、52.27 μmol·cm -2 ·h -1 and 61.55 μmol·cm -2 ·h -1 The apparent quantum efficiencies were 0.024%, 0.094%, 0.14%, 0.54%, 1.0% and 1.2%, respectively. It can be seen from the results that the product yields were very small when Ni-CoTCPP, GO and TiO2NTs were used as photocatalysts. The photocatalytic activity of Ni-CoTCPP / GO / TiO2NTs obtained by co-modifying TiO2NTs with Ni-CoTCPP and GO for CO2 reduction to generate CH4 was significantly improved, which was better than Ni-CoTCPP / TiO2NTs and GO / TiO2NTs, and the CH4 yield was 61.55 μmol·cm -2 ·h -1 The apparent quantum efficiency is 1.2%, which is about 8.6 times that of TiO2NTs material. This shows the excellent performance of this photocatalyst in photocatalytic CO2 reduction.
[0050] In addition, Ni-CoTCPP / GO / TiO2NTs was selected for 10 cycles of photocatalytic experiments. Figure 6 As shown in the figure, after 10 cycles, the CH4 yield increased from 61.55 μmol·cm -2 ·h -1 Reduced to 58.53 μmol·cm -2 ·h -1 , the CH4 yield decreased by about 5%, indicating that Ni-CoTCPP / GO / TiO2NTs has good recyclability. After 10 cycles, the recovered samples were analyzed by XRD, as shown in Figure 7As shown in the figure, it was found that the crystal structure of Ni-CoTCPP / GO / TiO2NTs did not change significantly before and after the reaction, which further verified that the catalyst had good stability. The addition of GO accelerated the transfer and capture of electrons and increased the absorption of light. Due to the high charge mobility of GO, the recombination of photogenerated carriers was largely suppressed, which significantly improved the photostability of Ni-CoTCPP / GO / TiO2NTs.
Claims
1. A bimetallic porphyrin / GO / TiO2 nanotube composite photocatalytic material, characterized in that: The bimetallic porphyrin / GO / TiO2 nanotube composite photocatalytic material is prepared by the following preparation method: Step 1, preparation of Ni-CoTCPP: weigh 0.02 mmol of Ni (NO3)2・6H2O) and 10 mg of PVP, dissolve in a mixture of 18-30 mL of DMF and anhydrous ethanol to obtain solution A; then take 0.01 mmol of CoTCPP and dissolve it in a mixed solution of 6-10 mL of DMF and anhydrous ethanol, ultrasonically dissolve it in an ultrasonic cleaner for 10-20 min, and then take it out to obtain solution B; add solution B dropwise to solution A, and finally transfer the mixed solution to a 50 mL polytetrafluoroethylene-lined reactor, and react at 70-100°C for 2-4 h; after the reaction is completed, transfer it to a centrifuge tube, add anhydrous ethanol, wash and centrifuge to obtain the desired product Ni-CoTCPP; Step 2: Preparation of Ni-CoTCPP / TiO2NTs: Ni-CoTCPP was prepared at a concentration of 1×10 -5 mol / L concentration was dissolved in DMF to prepare a bimetallic porphyrin solution; TiO2NTs were immersed in the porphyrin solution and magnetically stirred for 4-6 h, the titanium foil was taken out with tweezers, and dried at room temperature to obtain bimetallic porphyrin-sensitized TiO2NTs, namely Ni-CoTCPP / TiO2NTs; Step 3. Preparation of Ni-CoTCPP / GO / TiO2NTs: Immerse Ni-CoTCPP / TiO2NTs in a 0.5 mg / mL GO suspension, stir magnetically for 4-6 h, remove the titanium foil with tweezers, and dry at room temperature to obtain Ni-CoTCPP / GO / TiO2NTs.
2. The bimetallic porphyrin / GO / TiO2 nanotube composite photocatalytic material according to claim 1, characterized in that: In the mixed solution of DMF and anhydrous ethanol, the volume ratio of DMF to anhydrous ethanol is 3:
1.
3. The bimetallic porphyrin / GO / TiO2 nanotube composite photocatalytic material according to claim 2, characterized in that: The preparation method of CoTCPP is as follows: 79 mg TCPP and 75 mg (CH3COO)2Co·4H2O powder are weighed, added into a mixed solution of 150-300 mL DMF and acetic acid, refluxed at 100-150 °C for 1-3 h, and after the reaction is completed, cooled and 400-600 mL water is added to precipitate the product; After filtering, washing and drying, CoTCPP was obtained.
4. The bimetallic porphyrin / GO / TiO2 nanotube composite photocatalytic material according to claim 3, characterized in that: In the DMF and acetic acid mixed solution, the volume ratio of DMF to acetic acid is 1:
1.
5. The bimetallic porphyrin / GO / TiO2 nanotube composite photocatalytic material according to claim 4, characterized in that: The preparation method of TCPP is as follows: 3.00 g of p-carboxybenzaldehyde and 60-90 mL of propionic acid are mixed and poured into a three-necked flask with a capacity of 250 mL, and stirred for 0.25-1 h under the action of a magnetic stirrer; then heated to 100-150 ° C, 1.4 mL of freshly distilled pyrrole and 8-15 mL of propionic acid are measured and mixed, and then dropwise added into the three-necked flask, the dropping time is maintained at 5-15 min, heated to reflux for 3-5 h, and naturally cooled to room temperature after the reaction is completed, 8-15 mL of ethanol is continued to be added and stirred evenly, and then placed in a 4 ° C cold water bath for reaction for 15-20 h; suction filtration is performed, the filter cake is rinsed with a CH3OH solution for multiple times, and then the filter cake is subjected to Soxhlet extraction with CH3OH until the washing liquid is clear, and the obtained purple filter cake is recrystallized with a methanol-chloroform solution to obtain TCPP.
6. The bimetallic porphyrin / GO / TiO2 nanotube composite photocatalytic material according to claim 5, characterized in that: The preparation method of GO: 1) Dissolve 2 g of natural flake graphite and 2 g of NaNO3 in 92 mL of concentrated H2SO4 and stir in an ice bath for 10 min until uniform; 2) Slowly add 9 g KMnO4 in batches, control the system temperature at 0-5 °C and react for 2 h; 3) Then slowly raise the temperature of the water bath to 35 °C and continue the reaction for 2 h. Then add 90 mL of deionized water and raise the temperature to 98 °C for a constant temperature reaction for 0.5 h. 4) After cooling naturally to room temperature, add 180 mL of deionized water and drop 10 mL of 30% H2O2 into the solution until the solution turns bright yellow; 5) The solution was washed with 1 mol / L HCl and then centrifuged with deionized water until the pH value of the solution was close to 7.
0. Finally, the supernatant was ultrasonically treated and dried to obtain GO.
7. The bimetallic porphyrin / GO / TiO2 nanotube composite photocatalytic material according to claim 6, characterized in that: The preparation method of the TiO2NTs: 1) 1.5 cm² titanium foil was ultrasonically cleaned in acetone, anhydrous ethanol and deionized water for 15 min, and dried at room temperature; 2) Use the cleaned titanium foil as the anode electrode and the platinum foil as the counter electrode, immerse them in an electrolyte consisting of ethylene glycol, 2 vol% deionized water and 0.3 wt% NH4F, stir the electrolyte in a constant temperature water bath at 20 °C, adjust the constant voltage power supply voltage to 60 V for primary oxidation, and control the oxidation time to 0.5 h; 3) Place the titanium sheet after primary oxidation in deionized water and ultrasonically wash away the formed oxide film, rinse it clean and dry it; 4) The titanium sheet obtained in step 3) is subjected to secondary anodization according to the method of step 2), and after completion, the generated TiO2NTs are washed with deionized water and dried; 5) The dried TiO2NTs were calcined in a muffle furnace at 450 °C for 3 h at a heating rate of 2 °C / min to obtain TiO2NTs.
8. An application of the bimetallic porphyrin / GO / TiO2 nanotube composite photocatalyst according to claim 7, characterized in that: The bimetallic porphyrin / GO / TiO2 nanotube composite photocatalytic material is used for photocatalytic reduction of CO2.
9. The use of the bimetallic porphyrin / GO / TiO2 nanotube composite photocatalyst according to claim 8, characterized in that: The method for using the bimetallic porphyrin / GO / TiO2 nanotube composite photocatalytic material for photocatalytic reduction of CO2 is as follows: The photocatalytic reduction CO2 device includes a photocatalytic reactor and a water vapor generator. The light source is placed above the photocatalytic reactor. The photocatalytic reactor and the light source are placed in a photocatalytic reaction protection cover. The light source is a 500 W xenon lamp light source. The CO2 gas pipeline is connected to the photocatalytic reactor after passing through the water vapor generator. The bimetallic porphyrin / GO / TiO2 nanotube composite photocatalytic material is placed on a titanium sheet, and the titanium sheet is placed in the photocatalytic reactor. Before the reaction, check the airtightness of the photocatalytic reduction CO2 device and remove the impurity gas in the photocatalytic reactor; During the reaction, CO2 gas passes through the water vapor generator and maintains a flow rate of 60 mL / min, so that the mixed gas formed by CO2 and water vapor enters the photocatalytic reactor. When the pressure of CO2 and water vapor in the photocatalytic reactor reaches 1.5 atm, the circulating cooling water pump is turned on to complete the photocatalytic reduction of CO2 under continuous illumination.
Citation Information
Cited By
Novel MOF composite material and preparation method and application thereof
CN121495133A
A novel MOF composite material and a preparation method and application thereof
CN121495133B
Metalloporphyrin-bismuth oxyhalide composite catalyst with amide functional interface as well as preparation method and application of metalloporphyrin-bismuth oxyhalide composite catalyst
CN121732243A